MEMBANGUN KARAKTER ANAK DIDIK MELALUI KETELADANAN KEPEMIMPINAN KEPALA SEKOLAH/MADRASAH - Suaidi Suaidi; Istinganatul ngulwiyah.; Jakaria Jakaria (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2021)
Character is a value that related to human personality, based on religious norms, customs and social cultures. A strong nation is a nation that has a good character and personality. On the other hand, a weak nation that commits injustice and bad behaviour. Progress in technology has a close correlation with human personality that gives positive and negative impacts. There are many negative impacts from technology progress: instant culture, the number of views on television and social media that broadcast pornography and violence that can affect the mental and moral young generation. Negative impacts from technology progress influences student character at all levels of education. Students who have bad character are: lazy to study, coming late to the school, don’t care about friends and environment. Based on explanation here the writer is interested to do the research about the Importance of character education to be developed in schools by using exemplary leaders of educational institutions or schools. Character education must be given from an early age and elementary school, and it is must be actualized through the next level including at the university level. Considering the importance of character education in the context of education, the government implements an education system that emphasizes the importance of character education and national culture.